Chinese Herbal Medicine Xingnaojing Injection for Acute Ischemic Stroke: An Overview of Systematic Reviews and Meta-Analyses - Tian, Zi-Yu; Feng, Lu-Da; Xie, Yao; Xu, De-Hao; Zhang, Chong-Yang; Kong, Ling-Bo; An, Rong-Rong; Ma, Li-Fang; Robinson, Nicola; Gao, Ying; Liu, Jian-Ping (Frontiers in Pharmacology, 2021)
Xingnaojing injection (XNJ) is the only Chinese herbal injection approved for both intracerebral hemorrhage and ischemia stroke (IS) first aid on ambulances in China, many systematic reviews (SRs) and meta-analysis (MAs) of XNJ on stroke has been published. The purpose of this research was to evaluate and summarize the current evidence on XNJ for IS. A comprehensive search was conducted for SRs and MAs of XNJ on IS . Two authors independently identified SRs and MAs, extracted data, assessed the quality of SRs and MAs using the Assessment of Multiple Systematic Reviews 2 (AMSTAR 2) and assessed quality of evidence using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE). A total of 10 SRs met the inclusion criteria. The quality of included SRs using AMSTAR 2 were critically low as the critical items were poorly reported. Only 10% of SRs reported 50% of the 16 items, while the remaining 90% reported just less than half of items on AMSTAR 2. For GRADE, 7 (35%) of outcomes had low quality evidence, 10 (50%) with very low and 3 (15%) with moderate quality evidence. Very low to low quality of evidence indicated XNJ plus conventional therapy (CT) alleviated the neurological deficit of acute IS. Moderate quality evidence showed XNJ plus CT reduced mortality when compared to Danshen injection plus CT and very low quality evidence showed XNJ plus CT could not improve the degree of comma while low quality evidence indicated the opposite. Mild adverse events in CT group were less than that in XNJ plus CT group and there were no serious adverse events, but there was no statistical difference between the two groups. The included 10 SRs indicated that XNJ were used for acute IS, but only 4 SRs (40%) reported the course of disease. Conclusion: XNJ appears to be effective and safe for acute IS in improving the neurological deficits, but the evidence is not robust enough. However, whether administering XNJ immediately after or within 24 hours of IS is unknown due to lack of data. Well-designed large scale RCTs with measurable outcomes are required in future studies.